La actividad de un artesano en Las Indias: el platero Juan Manuel Pasmiño (1770-1811) - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1998)
The aim of this work is to write about the life of one of the most important silver craftsman in Cuenca, so as to explain the development of these group’s existente in the last years of the Spanish control, and to show how daily life was in those places. Apart from that, this study describes the everyday development of a particular social group in a city of secondary importance, although with certain relevance in the Kingdom of Quito territories, in the Spanish America.